Modeling retweeting behavior as a game: comparison to empirical results. Issue 88 (April 2016) - O'Leary, Daniel E.
Abstract: Twitter is one of the dominant social media, and the number of retweets is a key analytic descriptor of social media behavior. Unfortunately, there has been limited analysis and investigation of potential theories to explain empirical retweeting results. This paper uses social exchange theory and game theory to analyze a number of different previous empirical behavioral findings. In particular, the paper investigates games and network games between different potential retweeters by analyzing the relationships between their different groups of followers. In addition, cooperative retweeting settings, such as those in the Arab Spring revolutions, also are investigated for games between retweeters. Further, games between original tweeters and retweeters are analyzed using a "tit-for-tat" strategy for retweeting. Finally, this paper examines a game between an original tweeter and a retweeter for the problem of retweet hijacking. Throughout the focus is on modeling and explaining the empirical and anecdotal behavior of tweeters and retweeters using social exchange theory and game theory models. Highlights: Social exchange and game theory are used to model retweeting. Retweet behavior is modeled as a game and compared to previous empirical research. Multiple games between retweeters were investigated. A set theoretic approach to analyzing subsets of Twitter followers was used. Extended the use of games as mental representations to retweet behavior.